Inverse relationship between serum osteocalcin levels and nonalcoholic fatty liver disease in postmenopausal Chinese women with normal blood glucose levels - LUO Yu-qi; MA Xiao-jing; HAO Ya-ping; PAN Xiao-ping; XU Yi-ting; XIONG Qin; BAO Yu-qian; JIA Wei-ping (Acta Pharmacologica Sinica, 2017)
Aim: Osteocalcin is involved in the progression of nonalcoholic fatty liver disease (NAFLD) in animal models and humans. In this study we investigated the relationship between serum osteocalcin levels and NAFLD in postmenopausal Chinese women. Methods: A total of 733 postmenopausal women (age range: 41–78 years) with normal blood glucose levels were enrolled in this cross-sectional study. Women taking lipid-lowering or anti-hypertensive drugs were excluded. Serum osteocalcin levels were assessed using an electrochemiluminescence immunoassay. The degree of NAFLD progression for each subject was assessed through ultrasonography. The fatty liver index (FLI) of each subject was calculated to quantify the degree of liver steatosis. Results: The median level of serum osteocalcin for all subjects enrolled was 21.99 ng/mL (interquartile range: 17.84–26.55 ng/mL). Subjects with NAFLD had significantly lower serum osteocalcin levels (18.39 ng/mL; range: 16.03–23.64 ng/mL) compared with those without NAFLD (22.31 ng/mL; range: 18.55–27.06 ng/mL; P